PLANNING TO ENHANCE COMMUNICATION LINE RELIABILITY IN RURAL AREA OF CHEVRON PACIFIC INDONESIA - Edmond Febrinicko Armay; Furkon Hidayat; Arif Ranusaputro (Kodepena (Komunitas Dosen Penulis dan Peneliti Indonesia), 2020)
System modeling has been made in Chevron Pacific Indonesia by considering of existing network technology and transmission line. Availability of the existing network is 99.9964304%. Using Markov model, a planning analysis of reliability enhancement can be obtained in rural area of Chevron Pacific Indonesia between Kotabatak and Petapahan. Input parameters that are used are failure and repair rates from network devices, while output parameters of network reliability are system downtime and availability. Enhancement planning is divided into Plan 1 and Plan 2. Availability that is obtained in Plan 1 is 99.9966112%, while in Plan 2 is 99.9999998%. From calculations, it can be obtained that the availability increases 0.0001808% from the existing network to Plan 1, from Plan 1 to Plan 2 increases 0.0033886%, therefore from the existing network to Plan 2 increases 0.0035694%.